Entre o contorno legal da escravidão e o trabalhismo: a manutenção do racismo através de uma autonomia dependente - Rabelo, Danilo dos Santos (2021)
This present study intends to investigate the influence and participation of law, through the legal form of autonomy, in the sedimentation of a political-economic system that, beyond abolition, maneuvers racism as a central attribute of its cycles of exploitation. Therefore, it starts from the hypothesis that this legal category acted as a device that enabled the replacement of the bloody exploitation of Brazilian blacks, backed by an express legal contour, in the pre-abolition period, by contractual relations that, in the post-abolition period, precisely in the formation of Brazilian laborism, ideologically omitted racial inequalities and forged an appearance of inclusion and freedom. Thus, initially, the complex debate about racism is based on three horizons that seek to understand its sophisticated and modern guises. It analyzes as a cultural phenomenon, adaptable to the demands of the economic system and its ideological forms. Subsequently, it outlines the use of racism in the project for the formation of Brazil as a nation and, consequently, its handling in the social division of labor. In a third horizon, it analyzes how, in the post-abolition period, a social imaginary was created and fostered with the objective of ideologically normalizing the racialized social hierarchy and its cycles of exploitation. In the second chapter, it discusses the formation of Brazilian national law based on its main influence: the liberal legal culture. First, it points out the legal contour of slavery, the duality between the exclusion of the enslaved as a subject and its inclusion in the mechanisms of penal repression. Then it outlines how the liberal legalform acts as a necessary superstructure for the reproduction of capital, giving it legitimacy and security. In the third and last chapter, it traces a critical-comparative analysis of the centenary work “The Brazilian people and its evolution”, inserted in the 1920 census, written by the sociologist and one of the patrons of national laborism – Oliveira Vianna. In it, the arguments presented to achieve national development remain crossed by an ethnic-racial research based on whitening and the incongruity between black people and autonomy. Thereby, this text is analyzed from the category of “dependence” in Clóvis Moura, notably to understand the new forms and new arguments of racial oppression that will be forged with the formal end of slavery. Among them, institutionalized state projects, which in labor will represent the legal autonomy of blacks as dangerous to the new social structure and which, therefore, should be replaced by a laborious and obedient autonomy. It is concluded that, in the post-abolition period, in the replacement of slave labor for free work, the legal form of autonomy will not only hide the existing racial oppression, it will mean a new level of legal participation in the sedimentation of racism, at an intrinsic, controlled, not coded level.